2003
DOI: 10.1002/ajim.10185
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell cancer risk and occupational exposure to trichloroethylene: Results of a consecutive case‐control study in Arnsberg, Germany

Abstract: The study supports the human nephrocarcinogenicity of trichloroethylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 33 publications
(61 reference statements)
4
66
1
1
Order By: Relevance
“…All three of these studies reported strikingly elevated relative risks for renal cell cancer associated with TCE exposure. [167][168][169] The fi ndings contrast starkly with results from other investigations, and several serious methodological shortcomings of these studies have been noted, [170][171][172] limiting any conclusion that can be drawn. To date, seven occupational cohort studies have evaluated the relationship between TCE exposure and specifi c types of cancer.…”
Section: Occupationcontrasting
confidence: 88%
“…All three of these studies reported strikingly elevated relative risks for renal cell cancer associated with TCE exposure. [167][168][169] The fi ndings contrast starkly with results from other investigations, and several serious methodological shortcomings of these studies have been noted, [170][171][172] limiting any conclusion that can be drawn. To date, seven occupational cohort studies have evaluated the relationship between TCE exposure and specifi c types of cancer.…”
Section: Occupationcontrasting
confidence: 88%
“…However, renal cell cancer cases displayed a somewhat higher proportion of the homozygous GSTP1 313A wild type (GSTP1*A), although this was not statistically signiWcant ( 2 test: P = 0.1071, when using only the original controls of Brüning et al (2003); P = 0.0781 with inclusion of the additional controls). Conclusion The re-investigation does not conWrm the working hypothesis of an inXuence of the deletion polymorphisms of the glutathione S-transferases GSTT1 and GSTM1 on renal cell cancer development due to high occupational exposures to trichloroethylene.…”
mentioning
confidence: 87%
“…Exposure settings include occupational exposures in the aerospace and screw-cutting industries and exposure to the general population occurs through contaminated air, water, and soil. An increased risk of kidney cancer was reported in all of the studies in which there was a moderate to very high level of estimated TCE exposure (Henschler et al, 1995;Morgan et al, 1998;Vamvakas et al, 1998;Brüning et al, 2003;Raaschou-Nielsen et al, 2003;Zhao et al, 2005;Boice et al, 2006;Charbotel et al, 2006;Radican et al, 2008;Moore et al, 2010;Hansen et al, 2013), with most risk estimates being statistically significant. Additionally, positive exposureresponse relationships were reported in several case-control (Charbotel et al, 2006;Moore et al, 2010) and cohort studies (Zhao et al, 2005;Raaschou-Nielsen et al, 2003) using different exposure metrics.…”
Section: Cancermentioning
confidence: 96%